Performance Of Enterococcus Faecalis In The Production Of Methane Using Single And Double Phase Reactors - Zakarya, Irnis Azura (2011)
Production of methane via anaerobic digestion process is the method that already commercialized in the sustainable of renewable energy. The study on performance of Enterococcus faecalis (E. faecalis) in the production of methane is new research in co-digestion with food waste using single and double phase reactors. E. faecalis isolated from palm oil mill effluent (POME) that taken from holding pond at the nearest palm oil mill. Food waste collected from the university cafeterias were sorted out in three different groups which are group A (45% of rice, noodle), group B (30% of meat, fish) and group C (25% of vegetables).